PERAN IDENTITAS NASIONAL DALAM MENYATUKAN BANGSA INDONESIA - Putri, Jacinda Alline Yoriana; Feby, Chansa Adhilia Dhia (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Indonesia as an archipelago has a diversity of ethnicities, cultures, languages and religions that become the national identity as well as the strength of the nation. National identity, reflected in Pancasila and the motto Bhinneka Tunggal Ika, plays an important role in maintaining unity in a multicultural society. This article aims to examine the role of national identity in uniting the Indonesian nation through a literature review method. This research analyzes five accredited articles that discuss the role of Pancasila values in strengthening the sense of nationality, patriotism, and solidarity among citizens, especially in the era of globalization and technological development. The results show that the internalization of national identity values through education and social media is a key strategy in building a harmonious and equitable national character. By strengthening national identity, Indonesia is able to maintain its unity, sovereignty, and resilience to face the challenges of the times.